Spectroscopic Observation and Molecular Dynamics Simulation of Ga Surface Segregation in Liquid Pd–Ga Alloys. Issue 70 (6th November 2017) - Grabau, Mathias; Erhard, Jannis; Taccardi, Nicola; Calderon, Sandra Krick; Wasserscheid, Peter; Görling, Andreas; Steinrück, Hans‐Peter; Papp, Christian
Abstract: Liquid binary Pd–Ga alloys with low Pd contents of 0.8, 1.8, and 4.7 at % of Pd were examined as a function of sample temperature in ultra‐high vacuum by using angle‐resolved XPS. Upon cooling from 750 to 400 K, a pronounced temperature‐dependence of the Pd concentration in the liquid phase was observed, which was explained by the transition from the pure liquid phase to a two‐phase system, consisting of a solid Ga5 Pd phase and a Pd‐depleted liquid Pd–Ga alloy. In the liquid Pd–Ga alloy, Pd is always depleted from the topmost interface layer, as deduced from angle‐resolved XPS at 0 and 80° emission, independent of temperature and Pd concentration. This observation is interpreted as an inhomogeneous depth distribution function of Pd, that is, the segregation of Ga to the surface of the liquid phase. The results of a DFT‐based molecular dynamics simulation (MD) independently show interfacial stratification of Ga and an inhomogeneous Pd distribution along the surface normal. The evaluation of the experimental data with a rigid layer model based on the MD calculations leads to excellent agreement with the simulation. Abstract : X‐ray photoelectron spectroscopy and DFT‐based molecular dynamics simulations determined an inhomogeneous depth distribution of the liquid metal catalyst Pd/Ga. Additionally, the Pd surface concentration in the examined liquid Pd–Ga alloys was was temperature dependent, which is ascribed to the formation of Pd‐rich Ga5 Pd particles in the liquid bulk. With increasing temperature, the Pd concentration in the surface near region of the liquid probed by XPS increases (see figure).